2018
DOI: 10.1302/0301-620x.100b1.bjj-2017-0600.r1
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of lateral unicondylar mobile bearing knee arthroplasty

Abstract: Our data, which consists of a high number of patients treated with mobile bearing UKA in the lateral compartment, indicates a high revision rate of 15% at five years with dislocation of the mobile bearing being the main reason for implant failure. Despite the good functional and clinical results and the high patient satisfaction in our study group, we therefore discontinued using mobile-bearing lateral UKA in favour of a fixed-bearing component. Cite this article: 2018;100-B:42-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 29 publications
3
45
0
3
Order By: Relevance
“…Several parameters have been identified as responsible for maintaining normal knee kinematics and thus avoiding common complications such as knee pain, polyethylene wear, and lateral compartment accelerated osteoarthritis in UKA. Limb alignment, component position and sizing, ligamentous and soft-tissue balancing, interprosthetic divergence, and maintenance of the inherent joint line are some of the surgical variables which have been shown to influence the clinical outcomes of UKA as well as its longevity [136] (Figs. 3, 4).…”
Section: Should We Use Cementless Implants Instead Of Cemented Ones?mentioning
confidence: 99%
“…Several parameters have been identified as responsible for maintaining normal knee kinematics and thus avoiding common complications such as knee pain, polyethylene wear, and lateral compartment accelerated osteoarthritis in UKA. Limb alignment, component position and sizing, ligamentous and soft-tissue balancing, interprosthetic divergence, and maintenance of the inherent joint line are some of the surgical variables which have been shown to influence the clinical outcomes of UKA as well as its longevity [136] (Figs. 3, 4).…”
Section: Should We Use Cementless Implants Instead Of Cemented Ones?mentioning
confidence: 99%
“…Accuracy of component positioning and limb alignment are important prognostic variables that affect implant survival and time to revision surgery following UKA [ 5 , 9 , 38 ]. CO UKA is performed using manually positioned alignment guides, limited intraoperative data on knee kinematics, and handheld milling devices or sawblades for bone resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, UKA is associated with decreased implant survivorship and increased revision rates compared with TKA [ 9 , 28 ]. Accuracy of component positioning and limb alignment are important prognostic variables that affect implant survival and time to revision surgery following UKA [ 5 , 9 , 38 ]. Consequently, techniques that improve the accuracy of implant positioning and limb alignment in UKA may help to improve long-term survivorship and reduce the burden of revision disease.…”
Section: Introductionmentioning
confidence: 99%
“…A multicentre study of 363 consecutive patients who underwent lateral UKA showed a high revision rate of 15% at 5 years with dislocation of the bearing (8.5% after 5 years) as a main reason for implant failure with the domed design. The authors concluded that despite the observed good functional and clinical results and the high patient satisfaction rate in this series, they decided to discontinue to use the domed mobile-bearing UKA instead of a fixed bearing component [41].…”
Section: Dislocation As a Mode Of Failure In Mobile-bearing Unismentioning
confidence: 92%